Tata Kelola dan Kinerja Perusahaan Keluarga di Indonesia - Lu, Shanice; Yopie, Santi (E-Jurnal Akuntansi, 2022)
Company performance is an important indicator for companies in assessing management effectiveness. This study aims to determine the effect of institutional ownership, managerial ownership, family ownership, family involvement, gender diversity of the board of directors, and the educational level of the CEO on the performance of family companies listed on the IDX for the 2017-2021 period. The sampling method used was purposive sampling with a total of 130 companies or 650 data meeting the criteria. The results of the study concluded that family ownership, family involvement, and gender diversity of the board of directors had no relationship to ROE and Tobin's Q. Institutional ownership did not affect ROE but had a positive relationship to Tobin's Q. Managerial ownership had a significant negative relationship to ROE but did not affect Tobin's Q. The education level of the CEO has a positive effect on ROE and Tobin's Q. Keywords: Firm Performance; Corporate Governance; Ownership Structure, Family Firm